A positive electrode sheet and preparation method thereof and lithium ion battery

By setting active coatings of cobalt-containing positive electrode materials with different cobalt content and particle sizes on the current collector surface of the positive electrode sheet of the lithium-ion battery, the problems of high cost and difficult performance improvement of the positive electrode materials are solved, and the low cost and high performance of the battery are achieved characteristic.

CN116779771BActive Publication Date: 2025-02-11GUANGZHOU GREATER BAY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310767815.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2025-02-11
Estimated Expiration
2043-06-27

AI Technical Summary

Technical Problem

The positive electrode materials of existing lithium-ion batteries are costly and it is difficult to improve high voltage cycling performance, fast charging performance and high temperature performance at the same time.

Method used

The first active coating and the second active coating are arranged in sequence on the surface of the current collector. The first active coating and the second active coating use cobalt-containing positive electrode materials with different cobalt content and particle size, respectively, and four cobalt-containing species are passed through The combination of the positive electrode material reduces the cost of the positive electrode material and improves the battery's power performance, fast charging performance, high voltage cycling performance and high temperature performance.

Benefits of technology

While ensuring energy density, the cost of the positive electrode material is reduced and the battery's power performance, fast charging performance, high voltage cycling performance and high temperature performance are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116779771B_ABST
    Figure CN116779771B_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode plate and a preparation method thereof and a lithium-ion battery, wherein the positive electrode plate comprises a current collector and a composite positive electrode active coating disposed on at least one side of the current collector; the composite positive electrode active coating comprises a first active coating and a second active coating, wherein the first active coating is disposed on the surface of the current collector, and the second active coating is disposed on the surface of the first active coating away from the current collector; the first active coating comprises a first cobalt-containing positive electrode material and a second cobalt-containing positive electrode material, wherein the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material have different cobalt contents and particle sizes; the second active coating comprises a third cobalt-containing positive electrode material and a fourth cobalt-containing positive electrode material, wherein the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material have different cobalt contents and particle sizes. The present invention can reduce the cost of positive electrode materials while ensuring energy density and can improve battery performance by combining four cobalt-containing positive electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a positive electrode sheet and a preparation method thereof and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have the characteristics of high specific capacity, low self-discharge, wide operating temperature range, high voltage platform, long cycle life, no memory effect and environmental friendliness. They have been widely used in mobile phones, laptops and power tools, and are gradually being promoted in the field of electric vehicles. At present, the commonly used positive electrode materials for lithium-ion batteries, such as nickel-cobalt-manganese ternary materials, contain cobalt elements. If the content of cobalt elements is high, it will lead to high costs, which is not conducive to promotion and use. Therefore, it is urgent to reduce costs. In addition, it often takes 7-8 hours to charge an electric car once. With the accelerated pace of life, people hope that lithium-ion batteries have good fast charging capabilities to shorten the battery charging time, and at the same time, higher and higher requirements are put forward for the cycle life of battery fast charging.

[0003] CN105374996A discloses a method for surface dry treatment of high-voltage nickel-cobalt-manganese ternary positive electrode materials. First, lithium salt is sieved and dispersed, and then weighed with nickel-cobalt-manganese hydroxide, and then added to a mixer for mixing, and mixed to obtain mixed raw powder; the mixed raw powder is loaded into a crucible and compacted, sintered in a high-temperature air atmosphere, and then cooled to a furnace discharge temperature of ≤80°C, the powder is taken out, and weakly broken, dispersed, and sieved in a drying room to obtain a highly dispersed nickel-cobalt-manganese ternary material matrix; the highly dispersed nickel-cobalt-manganese ternary material matrix and the coating agent A are weighed in a molar ratio of 1: (0.1-0.001) and added to a grinding mixer for mixing, so that they are mixed and contacted to obtain a mixed material; the mixed material is loaded into a crucible, sintered into a solid phase in a high-temperature air atmosphere, and then cooled to a furnace discharge temperature of ≤80°C, the powder is taken out, and sieved to obtain a high-voltage nickel-cobalt-manganese ternary material. The patent improves the capacity, cycle performance and high-temperature safety of the ternary material by means of coating.

[0004] CN104051725B discloses a method for preparing a high-voltage nickel cobalt manganese lithium oxide positive electrode material. First, metal elements are introduced into the nickel cobalt manganese lithium oxide primary material structure by doping to stabilize its structure; in the coating process of the primary material, the characteristics of urea slow release of hydroxide and the guiding effect of the inducer on the metal ions are used to create a rate-controllable homogeneous coating system. This coating method allows the metal compound to be slowly generated and orderly attached to the surface of the nickel cobalt manganese lithium oxide primary material, and finally forms a uniform coating film. Nickel cobalt manganese lithium oxide positive electrode material is synthesized by this preparation method to improve the cycle performance of the material under high voltage (4.35V) conditions. The above patents all use coating methods to improve the performance of the material, which is relatively cumbersome, and the above schemes are difficult to simultaneously improve high voltage cycle performance, fast charging performance and high temperature performance, and reduce costs.

[0005] Therefore, there is an urgent need for a solution to reduce material costs while improving the battery's high voltage cycle performance, fast charging performance, and high temperature performance. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a positive electrode plate and a preparation method thereof and a lithium-ion battery. The present invention sequentially arranges a first active coating and a second active coating on the surface of the current collector, and two cobalt-containing positive electrode materials with different cobalt contents and particle sizes are used in the first active coating and the second active coating, respectively. By combining four cobalt-containing positive electrode materials, the cost of the positive electrode material can be reduced while ensuring the energy density, and it is beneficial to improve the power performance, fast charging performance, high voltage cycle performance and high temperature performance of the battery.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a positive electrode plate, the positive electrode plate comprising a current collector and a composite positive electrode active coating disposed on at least one side surface of the current collector;

[0009] The composite positive electrode active coating comprises a first active coating and a second active coating, wherein the first active coating is disposed on the surface of the current collector, and the second active coating is disposed on the surface of the first active coating away from the current collector;

[0010] The first active coating layer comprises a first cobalt-containing positive electrode material and a second cobalt-containing positive electrode material, wherein the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material have different cobalt contents and particle sizes;

[0011] The second active coating layer comprises a third cobalt-containing positive electrode material and a fourth cobalt-containing positive electrode material, and the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material have different cobalt contents and particle sizes.

[0012] The present invention provides a positive electrode plate, wherein a first active coating and a second active coating are sequentially arranged on the surface of a current collector, and the first active coating comprises a first cobalt-containing positive electrode material and a second cobalt-containing positive electrode material having different cobalt contents and particle sizes, and the second active coating comprises a third cobalt-containing positive electrode material and a fourth cobalt-containing positive electrode material having different cobalt contents and particle sizes. The four cobalt-containing positive electrode materials are used in combination to reduce the cost of the positive electrode materials while ensuring the energy density, and are beneficial to improving the power performance, fast charging performance, high voltage cycle performance and high temperature performance of the battery, wherein the "high voltage" refers to a charging cut-off voltage greater than 4.3V.

[0013] Those skilled in the art should understand that the first active coating layer, in addition to the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material, may also include a binder and a conductive agent, wherein the binder includes but is not limited to polyvinylidene fluoride, and the mass fraction of the binder is 1-2%, for example, 1%, 1.5% or 2%, etc., based on the total mass of the first active coating layer as 100%; the conductive agent includes but is not limited to at least one of conductive carbon black, carbon nanotubes, carbon nanorods, vapor-grown carbon fibers, graphene and graphene oxide, and the mass fraction of the conductive agent is 1-3%, for example, 1%, 1.5%, 2%, 2.5% or 3%, etc., based on the total mass of the first active coating layer as 100%.

[0014] Those skilled in the art should understand that, in addition to the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material, the second active coating layer may also include a binder and a conductive agent, wherein the binder includes but is not limited to polyvinylidene fluoride, and the mass fraction of the binder is 1-2%, for example, 1%, 1.5% or 2%, etc., based on the total mass of the first active coating layer as 100%; the conductive agent includes but is not limited to at least one of conductive carbon black, carbon nanotubes, carbon nanorods, vapor-grown carbon fibers, graphene and graphene oxide, and the mass fraction of the conductive agent is 1-3%, for example, 1%, 1.5%, 2%, 2.5% or 3%, etc., based on the total mass of the first active coating layer as 100%.

[0015] Preferably, the types of binder and conductive agent used in the first active coating and the second active coating are the same.

[0016] Preferably, the current collector of the positive electrode plate comprises aluminum foil.

[0017] Preferably, the first cobalt-containing positive electrode material, the second cobalt-containing positive electrode material, the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material are all single crystal materials.

[0018] Positive electrode materials have evolved from polycrystalline materials to single crystal materials. Compared with polycrystalline materials, single crystal materials have obvious advantages in safety, stability and cycle life, and can operate at high voltage. However, in general, the cycle performance of lithium-ion batteries made of single crystal materials in high-voltage systems is extremely unstable, and the cycle life is difficult to guarantee, which severely limits the application of high-voltage fast-charging lithium-ion batteries. The solution of this application can solve the above problems.

[0019] Preferably, the first cobalt-containing positive electrode material, the second cobalt-containing positive electrode material, the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material independently include lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide.

[0020] Preferably, the chemical formulas of the first cobalt-containing positive electrode material, the second cobalt-containing positive electrode material, the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material are independently Li z Ni x Co y M (1-x-y) O2, wherein M includes Mn and / or Al, 1.03≤z≤1.07 can be, for example, 1.03, 1.04, 1.05, 1.06 or 1.07, etc., 0.6≤x≤0.7 can be, for example, 0.6, 0.62, 0.64, 0.66, 0.68 or 0.7, etc., 0.05≤y≤0.2 can be, for example, 0.05, 0.07, 0.1, 0.12, 0.14, 0.16, 0.18 or 0.2, etc.

[0021] Preferably, the cobalt content of the first cobalt-containing positive electrode material is lower than the cobalt content of the second cobalt-containing positive electrode material.

[0022] Preferably, based on the total molar amount of metal elements other than lithium as 100%, the cobalt content of the first cobalt-containing positive electrode material is 5-10%, for example, it can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, etc.

[0023] Preferably, based on the total molar amount of metal elements other than lithium as 100%, the cobalt content of the second cobalt-containing positive electrode material is 15-20%, for example, it can be 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5% or 20%, etc.

[0024] Preferably, the D50 particle size of the first cobalt-containing positive electrode material is greater than the D50 particle size of the second cobalt-containing positive electrode material.

[0025] Preferably, the D50 particle size of the first cobalt-containing positive electrode material is 4-5 μm, for example, it can be 4 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm or 5 μm.

[0026] Preferably, the D50 particle size of the second cobalt-containing positive electrode material is 3-3.8 μm, for example, 3 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm or 3.8 μm.

[0027] In the present invention, the first active coating layer uses a cobalt-containing positive electrode material with the above-mentioned cobalt content and particle size range. The second cobalt-containing positive electrode material with "high cobalt content and small particle size" can reduce the battery impedance, improve the power performance, and achieve fast charging of more than 4C; the first cobalt-containing positive electrode material with "low cobalt content and large particle size" can reduce material costs and improve the cycle stability of the battery at high voltage. The mixed use of the two can improve the fast charging performance and cycle performance at high voltage while achieving low cost. After several weeks (e.g., 500 weeks) of fast charging (e.g., 4C) at a high charging cut-off voltage (e.g., 4.4V), the capacity retention rate can still be maintained at a relatively high level (above 93%).

[0028] At the same time, the first active coating is located between the current collector and the second active coating, which can enhance the adhesion between the coating and the current collector and reduce the side reactions of the electrolyte. Since the first active coating contains a large proportion of positive electrode materials with "low cobalt content and large particle size", the specific surface area is small and the required adhesive content is small, which can enhance the adhesion with the current collector and reduce the side reactions with the electrolyte. At the same time, large-particle positive electrode materials can stabilize the material structure and avoid structural damage from the inside out of the material.

[0029] Preferably, based on the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material as 100%, the mass fraction of the first cobalt-containing positive electrode material is greater than or equal to the mass fraction of the second cobalt-containing positive electrode material.

[0030] Preferably, based on the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material as 100%, the mass fraction of the first cobalt-containing positive electrode material is 50-90%, for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc., preferably 60-80%.

[0031] In the present invention, the first cobalt-containing positive electrode material with a larger mass fraction of "low cobalt content and large particle size" is used in the first active coating, which is conducive to improving performance under high voltage and reducing the cost of battery use. In the first active coating, when the content of the first cobalt-containing positive electrode material with "low cobalt content and large particle size" is too low, the cycle stability and high temperature performance of the battery under high voltage will deteriorate; when the content of the first cobalt-containing positive electrode material with "low cobalt content and large particle size" is too high, the power performance of the battery will deteriorate.

[0032] Preferably, the cobalt content of the third cobalt-containing positive electrode material is lower than the cobalt content of the fourth cobalt-containing positive electrode material.

[0033] Preferably, based on the total molar amount of metal elements other than lithium as 100%, the cobalt content of the third cobalt-containing positive electrode material is 5-10%, for example, it can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, etc.

[0034] Preferably, based on the total molar amount of metal elements other than lithium as 100%, the cobalt content of the fourth cobalt-containing positive electrode material is 15-20%, for example, it can be 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5% or 20%, etc.

[0035] Preferably, the D50 particle size of the third cobalt-containing positive electrode material is greater than the D50 particle size of the fourth cobalt-containing positive electrode material.

[0036] Preferably, the D50 particle size of the third cobalt-containing positive electrode material is 4-5 μm, for example, it may be 4 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm or 5 μm.

[0037] Preferably, the D50 particle size of the fourth cobalt-containing positive electrode material is 3-3.8 μm, for example, 3 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm or 3.8 μm.

[0038] In the present invention, the second active coating layer uses a cobalt-containing positive electrode material with the above-mentioned cobalt content and particle size range. The fourth cobalt-containing positive electrode material with "high cobalt content and small particle size" can reduce the battery impedance, improve the power performance, and achieve fast charging of more than 4C; the third cobalt-containing positive electrode material with "low cobalt content and large particle size" can reduce material costs and improve the cycle stability of the battery at high voltage. The mixed use of the two can improve the fast charging performance and cycle performance at high voltage while achieving low cost. After several weeks (e.g., 500 weeks) of fast charging (e.g., 4C) at a high charging cut-off voltage (e.g., 4.4V), the capacity retention rate can still be maintained at a relatively high level (above 93%).

[0039] At the same time, the second active coating is located on the surface of the first active coating away from the current collector. The positive electrode material with "high cobalt content and small particle size" accounts for a larger proportion in the second active coating, which is conducive to the rapid escape of lithium ions, thereby creating a better lithium ion escape channel to improve power performance.

[0040] In the present invention, the first active coating and the second active coating respectively select two cobalt-containing positive electrode materials (such as nickel cobalt manganese oxide lithium positive electrode materials) with specific cobalt content and particle size range, among which the cobalt-containing positive electrode material with "high cobalt content and small particle size" can reduce battery impedance, improve battery efficiency, and improve the discharge capacity retention rate of lithium batteries; the cobalt-containing positive electrode material with "low cobalt content and large particle size" is beneficial to improving battery stability, reducing side reactions of surface positive electrode materials, and improving battery stability and high temperature performance under high voltage. At the same time, low cobalt content can reduce battery cost, effectively solving the problem of high cost of using high Co content in the prior art, and can also solve the problems of poor high voltage cycle stability of small particle size materials and poor power performance of large particle size materials.

[0041] Preferably, the third cobalt-containing positive electrode material and the first cobalt-containing positive electrode material have the same cobalt content and particle size.

[0042] Preferably, the fourth cobalt-containing positive electrode material and the second cobalt-containing positive electrode material have the same cobalt content and particle size.

[0043] Preferably, based on the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material being 100%, the mass fraction of the third cobalt-containing positive electrode material is less than or equal to the mass fraction of the fourth cobalt-containing positive electrode material.

[0044] Preferably, based on the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material as 100%, the mass fraction of the third cobalt-containing positive electrode material is 10-50%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc., preferably 20-40%.

[0045] In the second active coating, when the content of the third cobalt-containing positive electrode material with "low cobalt content and large particle size" is too low, the cycle stability of the battery under high voltage will deteriorate; when the content of the third cobalt-containing positive electrode material with "low cobalt content and large particle size" is too high, the power performance will decrease.

[0046] In the present invention, the use of a fourth cobalt-containing positive electrode material with a larger mass fraction of "high cobalt content and small particle size" in the second active coating is beneficial to reducing the ionic impedance of the battery, thereby facilitating the embedding of lithium ions.

[0047] In the present invention, by adjusting the proportion of the fourth cobalt-containing positive electrode material in the second active coating, a structure can be formed in which the fourth cobalt-containing positive electrode material with "high cobalt content and small particle size" surrounds the third cobalt-containing positive electrode material with "low cobalt content and large particle size", forming a positive electrode structure with a surface Co-rich gradient. The Co-rich surface has lower rigidity and can expand effectively to alleviate particle damage caused by internal expansion and surface compression stress, and at the same time can form a better lithium ion transmission channel, thereby improving the fast charging performance and cycle stability of the product. The blended low cobalt content and large particle size cobalt-containing positive electrode material can reduce the surface active reaction area, reduce the side reaction of the surface small particle size cobalt-containing positive electrode material with the electrolyte, and avoid the problem of poor cycle stability during fast charging under high voltage.

[0048] In the present invention, the content of the first cobalt-containing positive electrode material with "low cobalt content and large particle size" in the first active coating is increased, which reduces the material cost while ensuring the energy density. At the same time, compared with the first active coating, the content of the fourth cobalt-containing positive electrode material with "high cobalt content and small particle size" in the second active coating is increased, which is beneficial to the improvement of the power performance, fast charging performance and high-voltage cycle performance of the electrode piece. By adjusting the content of the two cobalt-containing positive electrode materials in each layer of the positive electrode active coating, the positive electrode piece has low cost and excellent power performance.

[0049] Preferably, based on the total mass of the first active coating and the second active coating being 100%, the mass fraction of the second active coating is greater than the mass fraction of the first active coating.

[0050] Preferably, based on the total mass of the first active coating and the second active coating as 100%, the mass fraction of the second active coating is 55-95%, for example, it can be 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or 95%, etc., preferably 60-70%.

[0051] In the present invention, controlling the mass ratio of the first active coating and the second active coating within the above range is beneficial to improving the power performance of the battery and the cycle performance under high voltage, while improving the high temperature performance under full-charge storage; when the mass ratio of the second active coating is greater than 50%, the battery can exhibit excellent power performance.

[0052] Preferably, based on the total mass of the first active coating and the second active coating as 100%, the total mass fraction of the first cobalt-containing positive electrode material, the second cobalt-containing positive electrode material, the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material is 94-97%, for example, it can be: 94%, 94.5%, 95%, 95.5%, 96%, 96.5% or 97%, etc.

[0053] Preferably, the single-surface density of the first active coating is 3.45-5.6 mg / cm2 , for example, it can be 3.45 mg / cm 2 、3.5mg / cm 2 、3.55mg / cm 2 、3.6mg / cm 2 、3.7mg / cm 2 、3.8mg / cm 2 、3.9mg / cm 2 , 4mg / cm 2 , 4.1mg / cm 2 , 4.2mg / cm 2 , 4.3mg / cm 2 , 4.5mg / cm 2 , 4.7mg / cm 2 , 4.9mg / cm 2 , 5mg / cm 2 , 5.1mg / cm 2 , 5.2mg / cm 2 , 5.3mg / cm 2 , 5.5mg / cm 2 or 5.6 mg / cm 2 wait.

[0054] Preferably, the single-surface density of the second active coating is 6.9-9.8 mg / cm 2 , for example, it can be 6.9 mg / cm 2 , 7mg / cm 2 、7.2mg / cm 2 、7.4mg / cm 2 、7.6mg / cm 2 、7.8mg / cm 2 , 8mg / cm 2 、8.2mg / cm 2 、8.4mg / cm 2 、8.6mg / cm 2 、8.8mg / cm 2 , 9mg / cm 2 , 9.2mg / cm 2 , 9.4mg / cm 2 、9.6mg / cm 2 or 9.8 mg / cm 2 wait.

[0055] Preferably, the single-surface density of the composite positive electrode active coating is 11.5-14 mg / cm 2 , for example, it can be 11.50 mg / cm 2 , 12mg / cm 2, 12.5mg / cm 2 、13mg / cm 2 、13.2mg / cm 2 、13.5mg / cm 2 or 14 mg / cm 2 wait.

[0056] Preferably, the compaction density of the composite positive electrode active coating is 3.3-3.5 g / cm 3 , for example, it can be 3.3 g / cm 3 、3.35mg / cm 3 、3.4mg / cm 3 、3.45mg / cm 3 or 3.5 mg / cm 3 wait.

[0057] In the present invention, the surface density and compaction density are controlled within the above range, which is beneficial for the prepared lithium-ion battery to have excellent fast charging performance and high-temperature cycle performance.

[0058] In a second aspect, the present invention provides a method for preparing the positive electrode sheet as described in the first aspect, the preparation method comprising:

[0059] Applying a first active coating slurry and a second active coating slurry on at least one side of the current collector, wherein the coating of the first active coating slurry and the second active coating slurry is performed by method one or method two, and drying to obtain the positive electrode sheet;

[0060] Wherein, the first method includes: applying a first active coating slurry and a second active coating slurry at the same time, wherein the first active coating slurry is applied on the surface of the current collector, and the second active coating slurry is applied on a side of the first active coating slurry away from the current collector;

[0061] The second method comprises: firstly applying a first active coating slurry, drying to obtain a first active coating, and then applying a second active coating slurry on a side of the first active coating away from the current collector;

[0062] The first active coating slurry comprises a first cobalt-containing positive electrode material and a second cobalt-containing positive electrode material, wherein the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material have different cobalt contents and particle sizes;

[0063] The second active coating slurry includes a third cobalt-containing positive electrode material and a fourth cobalt-containing positive electrode material, and the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material have different cobalt contents and particle sizes.

[0064] Those skilled in the art should understand that the first active coating slurry, in addition to the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material, also includes a binder, a conductive agent and a solvent; the second active coating slurry, in addition to the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material, also includes a binder, a conductive agent and a solvent; preferably, the first active coating and the second active coating include the same type of binder, conductive agent and solvent.

[0065] Optionally, the method 1 is carried out using a dual-die coating device, which adjusts the coating weight of each layer by adjusting the pressure of each die head; the electrode is dried during the coating process; after drying, the electrode is rolled to achieve the required compaction density.

[0066] Preferably, the viscosity of the first active coating slurry is 7000-12000 mPa·s, for example, it may be 7000 mPa·s, 7500 mPa·s, 8000 mPa·s, 8500 mPa·s, 9000 mPa·s, 9500 mPa·s, 10000 mPa·s, 10500 mPa·s, 11000 mPa·s, 11500 mPa·s or 12000 mPa·s, etc., preferably 8000-10000 mPa·s.

[0067] Preferably, the viscosity of the second active coating slurry is 2000-6000 mPa·s, for example, it may be 2000 mPa·s, 2500 mPa·s, 3000 mPa·s, 3500 mPa·s, 4000 mPa·s, 4500 mPa·s, 5000 mPa·s, 5500 mPa·s or 6000 mPa·s, etc., preferably 3000-5000 mPa·s.

[0068] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet described in the first aspect.

[0069] The lithium-ion battery of the present invention adopts the positive electrode plate as described in the first aspect, which can take into account the fast charging performance of the battery and the cycle stability and high temperature performance under high voltage.

[0070] Preferably, the lithium-ion battery further comprises a negative electrode plate.

[0071] Preferably, the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer coated on at least one side surface of the negative electrode current collector.

[0072] Preferably, the negative electrode current collector comprises copper foil, and the copper foil comprises carbon-coated copper foil and / or plain copper foil.

[0073] Preferably, the negative electrode active material in the negative electrode active material layer includes at least one of artificial graphite, silicon-oxygen material and silicon-carbon material, preferably fast-charging artificial graphite.

[0074] Preferably, the particle size D50 of the negative electrode active material is 11-15 μm, for example, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm or 15 μm.

[0075] Preferably, based on the total mass of the negative electrode active material layer being 100%, the mass content of the negative electrode active material is 94-96%, for example, 94%, 94.5%, 95%, 95.5% or 96%.

[0076] Preferably, the single surface density of the negative electrode active material layer is 7.5-9 mg / cm 2 , for example, it can be 7.5 mg / cm 2 , 8mg / cm 2 、8.5mg / cm 2 or 9mg / cm 2 wait.

[0077] Preferably, the compaction density of the negative electrode active material layer is 1.5-1.6 g / cm 3 , for example: 1.5g / cm 3 , 1.52g / cm 3 , 1.54g / cm 3 , 1.56g / cm 3 , 1.58g / cm 3 or 1.6 g / cm 3 wait.

[0078] Preferably, the N / P of the lithium-ion battery is set to 1.12-1.15, for example, 1.12, 1.13, 1.14 or 1.15, etc. The N / P refers to the ratio of the negative electrode reversible surface capacity to the positive electrode reversible surface capacity in the same stage and under the same operating conditions.

[0079] Preferably, the lithium ion battery comprises a separator.

[0080] Preferably, the diaphragm comprises a ceramic coated diaphragm.

[0081] Preferably, the lithium-ion battery comprises positive and negative electrode tabs.

[0082] Preferably, the positive and negative electrode tabs include aluminum electrode tabs and / or copper-plated nickel electrode tabs.

[0083] Preferably, the lithium-ion battery comprises an aluminum-plastic packaging film.

[0084] Preferably, the lithium-ion battery comprises an electrolyte.

[0085] The electrolyte of the lithium-ion battery of the present invention adopts an electrolyte that takes both fast charging and high voltage into consideration.

[0086] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0087] Compared with the prior art, the present invention has the following beneficial effects:

[0088] The present invention provides a positive electrode plate, wherein a first active coating and a second active coating are sequentially arranged on the surface of a current collector, and the first active coating comprises a first cobalt-containing positive electrode material and a second cobalt-containing positive electrode material having different cobalt contents and particle sizes, and the second active coating comprises a third cobalt-containing positive electrode material and a fourth cobalt-containing positive electrode material having different cobalt contents and particle sizes. The four cobalt-containing positive electrode materials are used in combination to reduce the cost of the positive electrode materials while ensuring the energy density, and are beneficial to improving the power performance, fast charging performance, high voltage cycle performance and high temperature performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0089] Figure 1 A schematic diagram of a positive electrode sheet provided in Example 1 of the present invention;

[0090] Among them, 1-current collector; 2-first active coating; 3-second active coating. DETAILED DESCRIPTION

[0091] It should be understood that in the description of the present invention, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first", "second", etc. may explicitly or implicitly include one or more of the features.

[0092] It should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "disposed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood by specific circumstances.

[0093] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0094] Example 1

[0095] This embodiment provides a positive electrode sheet, such as Figure 1 As shown, it includes a current collector 1 and a composite positive electrode active coating disposed on both sides of the current collector 1, the composite positive electrode active coating on each side includes a first active coating 2 and a second active coating 3, the first active coating 2 is disposed on the surface of the current collector 1, and the second active coating 3 is disposed on the surface of the first active coating 2 away from the current collector 1, wherein the current collector 1 is an aluminum foil;

[0096] The first active coating 2 comprises a first cobalt-containing positive electrode material, a second cobalt-containing positive electrode material, a conductive agent and a binder, wherein the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material are both single-crystal nickel cobalt manganese oxide positive electrode materials; based on the total molar amount of metal elements other than lithium being 100%, the cobalt content of the first cobalt-containing positive electrode material is 7%, the D50 particle size is 4.0 μm, and its chemical formula is Li 1.03 (Ni 0.65 Co 0.07 Mn 0.28 )O2; based on the total molar amount of metal elements other than lithium as 100%, the cobalt content of the second cobalt-containing positive electrode material is 15%, the D50 particle size is 3.3μm, and its chemical formula is Li 1.03 (Ni 0.6 Co 0.15 Mn 0.25 )O2; taking the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material as 100%, the mass fraction of the first cobalt-containing positive electrode material is 80%; the binder is polyvinylidene fluoride (PVDF), the conductive agent is a composite conductive agent of carbon black and carbon nanotubes, the composite ratio of carbon black and carbon nanotubes is 2:1, and the mass ratio of the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material to the conductive agent and the binder is 95%:3%:2%;

[0097] The second active coating 3 comprises a third cobalt-containing positive electrode material, a fourth cobalt-containing positive electrode material, a conductive agent and a binder, wherein the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material are both single-crystal nickel cobalt manganese oxide positive electrode materials; based on the total molar amount of metal elements other than lithium being 100%, the cobalt content of the third cobalt-containing positive electrode material is 7%, the D50 particle size is 4.0 μm, and its chemical formula is Li 1.03 (Ni 0.65 Co 0.07 Mn 0.28 )O2; based on the total molar amount of metal elements other than lithium as 100%, the cobalt content of the fourth cobalt-containing positive electrode material is 15%, the D50 particle size is 3.3μm, and its chemical formula is Li 1.03 (Ni 0.6 Co 0.15 Mn 0.25)O2; taking the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material as 100%, the mass fraction of the third cobalt-containing positive electrode material is 20%; the binder is polyvinylidene fluoride (PVDF), the conductive agent is a composite conductive agent of carbon black and carbon nanotubes, the composite ratio of carbon black and carbon nanotubes is 2:1, and the mass ratio of the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material to the conductive agent and the binder is 95%:3%:2%;

[0098] The single-surface density of the first active coating 2 is 4.8 mg / cm 2 The single-surface density of the second active coating 3 is 7.2 mg / cm 2 , so that the mass fraction of the second active coating is 60% based on the total mass of the first active coating and the second active coating as 100%; the total mass fraction of the first cobalt-containing positive electrode material, the second cobalt-containing positive electrode material, the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material is 95% based on the total mass of the first active coating 2 and the second active coating 3 as 100%; the single-surface surface density of the composite positive electrode active coating is 12 mg / cm 2 The average compacted density is 3.5g / cm 3 .

[0099] This embodiment also provides a method for preparing the positive electrode sheet, comprising:

[0100] Firstly, a first active coating slurry is coated on both sides of the current collector, and the first active coating is obtained after drying, and then a second active coating slurry is coated on the surface of the first active coating on each side away from the current collector, and the positive electrode sheet is obtained after drying;

[0101] Among them, the first active coating slurry includes a first cobalt-containing positive electrode material, a second cobalt-containing positive electrode material, PVDF, carbon black and carbon nanotubes composite conductive agent and a solvent, the solvent is N-methylpyrrolidone (NMP), and the slurry viscosity is 7500mPa·s; the second active coating slurry includes a third cobalt-containing positive electrode material, a fourth cobalt-containing positive electrode material, PVDF, carbon black and carbon nanotubes composite conductive agent and a solvent, the solvent is NMP, and the slurry viscosity is 500mPa·s.

[0102] Example 2

[0103] This embodiment provides a positive electrode sheet, comprising a current collector and a composite positive electrode active coating disposed on both sides of the current collector, wherein the composite positive electrode active coating on each side comprises a first active coating and a second active coating, wherein the first active coating is disposed on the surface of the current collector, and the second active coating is disposed on the surface of the first active coating away from the current collector, wherein the current collector is an aluminum foil;

[0104] The first active coating comprises a first cobalt-containing positive electrode material, a second cobalt-containing positive electrode material, a conductive agent and a binder, wherein the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material are both single-crystal nickel cobalt manganese oxide positive electrode materials; based on the total molar amount of metal elements other than lithium being 100%, the cobalt content of the first cobalt-containing positive electrode material is 5%, the D50 particle size is 5 μm, and its chemical formula is Li 1.03 (Ni 0.60 Co 0.05 Mn 0.35 )O2; based on the total molar amount of metal elements other than lithium as 100%, the cobalt content of the second cobalt-containing positive electrode material is 17%, the D50 particle size is 3μm, and its chemical formula is Li 1.03 (Ni 0.65 Co 0.17 Mn 0.28 )O2; taking the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material as 100%, the mass fraction of the first cobalt-containing positive electrode material is 50%; the binder is PVDF, the conductive agent is a composite conductive agent of carbon black and carbon nanotubes, the composite ratio of carbon black and carbon nanotubes is 2:1, and the mass ratio of the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material to the conductive agent and the binder is 95%:3%:2%;

[0105] The second active coating comprises a third cobalt-containing positive electrode material, a fourth cobalt-containing positive electrode material, a conductive agent and a binder, wherein the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material are both single crystal nickel cobalt manganese oxide positive electrode materials; based on the total molar amount of metal elements other than lithium being 100%, the cobalt content of the third cobalt-containing positive electrode material is 5%, the D50 particle size is 5 μm, and its chemical formula is Li 1.03 (Ni 0.60 Co 0.05 Mn 0.35 )O2; based on the total molar amount of metal elements other than lithium as 100%, the cobalt content of the fourth cobalt-containing positive electrode material is 17%, the D50 particle size is 3μm, and its chemical formula is Li 1.03 (Ni 0.65 Co 0.17 Mn 0.28 )O2; taking the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material as 100%, the mass fraction of the third cobalt-containing positive electrode material is 50%; the binder is PVDF, the conductive agent is a composite conductive agent of carbon black and carbon nanotubes, the composite ratio of carbon black and carbon nanotubes is 2:1, and the mass ratio of the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material to the conductive agent and the binder is 95%:3%:2%;

[0106] The single-surface density of the first active coating is 5.2 mg / cm 2The single-surface density of the second active coating is 9.66 mg / cm 2 , so that the mass fraction of the second active coating is 65% based on the total mass of the first active coating and the second active coating is 100%; the total mass fraction of the first cobalt-containing positive electrode material, the second cobalt-containing positive electrode material, the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material is 94% based on the total mass of the first active coating and the second active coating is 100%; the single-surface surface density of the composite positive electrode active coating is 13 mg / cm 2 The average compacted density is 3.4g / cm 3 .

[0107] This embodiment also provides a method for preparing the positive electrode sheet, comprising:

[0108] Using a double-die coating device to simultaneously coat both sides of the current collector, wherein the first active coating slurry and the second active coating slurry are simultaneously coated on each side surface, the first active coating slurry is coated on the surface of the current collector, and the second active coating slurry is coated on the side of the first active coating slurry away from the current collector, and the positive electrode sheet is obtained after drying;

[0109] Among them, the first active coating slurry includes a first cobalt-containing positive electrode material, a second cobalt-containing positive electrode material, PVDF, carbon black and carbon nanotubes composite conductive agent and a solvent, the solvent is NMP, and the slurry viscosity is 7000mPa·s; the second active coating slurry includes a third cobalt-containing positive electrode material, a fourth cobalt-containing positive electrode material, PVDF, carbon black and carbon nanotubes composite conductive agent and a solvent, the solvent is NMP, and the slurry viscosity is 2000mPa·s.

[0110] Example 3

[0111] This embodiment provides a positive electrode sheet, comprising a current collector and a composite positive electrode active coating disposed on both sides of the current collector, wherein the composite positive electrode active coating on each side comprises a first active coating and a second active coating, wherein the first active coating is disposed on the surface of the current collector, and the second active coating is disposed on the surface of the first active coating away from the current collector, wherein the current collector is an aluminum foil;

[0112] The first active coating comprises a first cobalt-containing positive electrode material, a second cobalt-containing positive electrode material, a conductive agent and a binder, wherein the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material are both single-crystal nickel cobalt manganese oxide positive electrode materials; based on the total molar amount of metal elements other than lithium being 100%, the cobalt content of the first cobalt-containing positive electrode material is 10%, the D50 particle size is 4.5 μm, and its chemical formula is Li 1.03 (Ni 0.6 Co 0.1 Mn 0.3)O2; based on the total molar amount of metal elements other than lithium as 100%, the cobalt content of the second cobalt-containing positive electrode material is 20%, the D50 particle size is 3.8μm, and its chemical formula is Li 1.03 (Ni 0.65 Co 0.2 Mn 0.15 )O2; taking the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material as 100%, the mass fraction of the first cobalt-containing positive electrode material is 60%; the binder is PVDF, the conductive agent is a composite conductive agent of carbon black and carbon nanotubes, the composite ratio of carbon black and carbon nanotubes is 2:1, and the mass ratio of the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material to the conductive agent and the binder is 95%:3%:2%;

[0113] The second active coating comprises a third cobalt-containing positive electrode material, a fourth cobalt-containing positive electrode material, a conductive agent and a binder, wherein the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material are both single crystal nickel cobalt manganese oxide positive electrode materials; based on the total molar amount of metal elements other than lithium being 100%, the cobalt content of the third cobalt-containing positive electrode material is 10%, the D50 particle size is 4.5 μm, and its chemical formula is Li 1.03 (Ni 0.6 Co 0.1 Mn 0.13 )O2; based on the total molar amount of metal elements other than lithium as 100%, the cobalt content of the fourth cobalt-containing positive electrode material is 20%, the D50 particle size is 3.8μm, and its chemical formula is Li 1.03 (Ni 0.65 Co 0.2 Mn 0.15 )O2; taking the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material as 100%, the mass fraction of the third cobalt-containing positive electrode material is 40%; the binder is PVDF, the conductive agent is a composite conductive agent of carbon black and carbon nanotubes, the composite ratio of carbon black and carbon nanotubes is 2:1, and the mass ratio of the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material to the conductive agent and the binder is 95%:3%:2%;

[0114] The single-surface density of the first active coating is 5.6 mg / cm 2 The single-sided surface density of the second active coating is 6.8 mg / cm 2 , so that the mass fraction of the second active coating is 55% based on the total mass of the first active coating and the second active coating is 100%; the total mass fraction of the first cobalt-containing positive electrode material, the second cobalt-containing positive electrode material, the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material is 97% based on the total mass of the first active coating and the second active coating is 100%; the single-surface surface density of the composite positive electrode active coating is 14 mg / cm 2The average compacted density is 3.5g / cm 3 .

[0115] This embodiment also provides a method for preparing the positive electrode sheet, comprising:

[0116] Using a double-die coating device to simultaneously coat both sides of the current collector, wherein the first active coating slurry and the second active coating slurry are simultaneously coated on each side surface, the first active coating slurry is coated on the surface of the current collector, and the second active coating slurry is coated on the side of the first active coating slurry away from the current collector, and the positive electrode sheet is obtained after drying;

[0117] Among them, the first active coating slurry includes a first cobalt-containing positive electrode material, a second cobalt-containing positive electrode material, PVDF, carbon black and carbon nanotubes composite conductive agent and a solvent, the solvent is NMP, and the slurry viscosity is 12000mPa·s; the second active coating slurry includes a third cobalt-containing positive electrode material, a fourth cobalt-containing positive electrode material, PVDF, carbon black and carbon nanotubes composite conductive agent and a solvent, the solvent is NMP, and the slurry viscosity is 6000mPa·s.

[0118] Example 4

[0119] The difference between this embodiment and embodiment 1 is that the mass fraction of the first cobalt-containing positive electrode material in the first active coating is adjusted to 70% (based on the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material as 100%); at the same time, the mass fraction of the third cobalt-containing positive electrode material in the second active coating is adjusted to 30% (based on the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material as 100%); and the mass fraction of the second active coating is adjusted to 95% (based on the total mass of the first active coating and the second active coating as 100%), and the rest is exactly the same as in embodiment 1.

[0120] Example 5

[0121] The difference between this embodiment and embodiment 1 is that the mass fraction of the first cobalt-containing positive electrode material in the first active coating is adjusted to 90% (based on the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material as 100%); at the same time, the mass fraction of the third cobalt-containing positive electrode material in the second active coating is adjusted to 10% (based on the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material as 100%); and the mass fraction of the second active coating is adjusted to 70% (based on the total mass of the first active coating and the second active coating as 100%), and the rest is exactly the same as in embodiment 1.

[0122] Example 6

[0123] The difference between this embodiment and embodiment 1 is that the mass fraction of the first cobalt-containing positive electrode material in the first active coating is adjusted to 48% (based on the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material as 100%), and the rest is exactly the same as embodiment 1.

[0124] Example 7

[0125] The difference between this embodiment and embodiment 1 is that the mass fraction of the first cobalt-containing positive electrode material in the first active coating is adjusted to 92% (based on the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material as 100%), and the rest is exactly the same as embodiment 1.

[0126] Example 8

[0127] The difference between this embodiment and embodiment 1 is that the mass fraction of the third cobalt-containing positive electrode material in the second active coating is adjusted to 8% (based on the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material as 100%), and the rest is exactly the same as embodiment 1.

[0128] Example 9

[0129] The difference between this embodiment and embodiment 1 is that the mass fraction of the third cobalt-containing positive electrode material in the second active coating is adjusted to 52% (based on the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material as 100%), and the rest is exactly the same as embodiment 1.

[0130] Example 10

[0131] The difference between this embodiment and embodiment 1 is that the mass fraction of the second active coating is adjusted to 50% (based on the total mass of the first active coating and the second active coating being 100%), and the rest is exactly the same as embodiment 1.

[0132] Embodiment 11

[0133] The difference between this embodiment and embodiment 1 is that the mass fraction of the second active coating is adjusted to 98% (based on the total mass of the first active coating and the second active coating being 100%), and the rest is exactly the same as embodiment 1.

[0134] Example 12

[0135] The difference between this embodiment and embodiment 1 is that the cobalt content of the third cobalt-containing positive electrode material is adjusted to 9%, and its chemical formula is Li 1.03 (Ni 0.65 Co 0.09 Mn 0.26 )O2, the D50 particle size is adjusted to 5.0 μm, and the cobalt content of the fourth cobalt-containing positive electrode material is adjusted to 18%, and its chemical formula is Li 1.03 (Ni0.6 Co 0.18 Mn 0.22 )O2, D50 particle size is adjusted to 3.5μm, and the rest is exactly the same as Example 1.

[0136] Comparative Example 1

[0137] The difference between this comparative example and Example 1 is that the second active coating is replaced by the first active coating, that is, two layers of the first active coating are provided on each side surface of the current collector, and the rest is exactly the same as Example 1.

[0138] Comparative Example 2

[0139] The difference between this comparative example and Example 1 is that the first active coating is replaced by the second active coating, that is, two layers of the second active coating are provided on each side surface of the current collector, and the rest is exactly the same as Example 1.

[0140] Comparative Example 3

[0141] The difference between this comparative example and Example 1 is that in the first active coating, the first cobalt-containing positive electrode material is replaced by the second cobalt-containing positive electrode material; in the second active coating, the fourth cobalt-containing positive electrode material is replaced by the third cobalt-containing positive electrode material, and the rest is exactly the same as Example 1.

[0142] Comparative Example 4

[0143] The difference between this comparative example and Example 1 is that in the first active coating, the second cobalt-containing positive electrode material is replaced by the first cobalt-containing positive electrode material; in the second active coating, the third cobalt-containing positive electrode material is replaced by the fourth cobalt-containing positive electrode material, and the rest is exactly the same as Example 1.

[0144] Comparative Example 5

[0145] The difference between this comparative example and Example 1 is that the second active coating is replaced by the first active coating, and the second cobalt-containing positive electrode material in the first active coating is replaced by the first cobalt-containing positive electrode material, and the rest is exactly the same as Example 1.

[0146] Comparative Example 6

[0147] The difference between this comparative example and Example 1 is that the second active coating is replaced by the first active coating, and the first cobalt-containing positive electrode material in the first active coating is replaced by the second cobalt-containing positive electrode material, and the rest is exactly the same as Example 1.

[0148] Comparative Example 7

[0149] The difference between this comparative example and Example 1 is that the first cobalt-containing positive electrode material in the first active coating is replaced by the second cobalt-containing positive electrode material, and the rest is exactly the same as Example 1.

[0150] Comparative Example 8

[0151] The difference between this comparative example and Example 1 is that the second cobalt-containing positive electrode material in the first active coating is replaced by the first cobalt-containing positive electrode material, and the rest is exactly the same as Example 1.

[0152] Comparative Example 9

[0153] The difference between this comparative example and Example 1 is that the third cobalt-containing positive electrode material in the second active coating is replaced by the fourth cobalt-containing positive electrode material, and the rest is exactly the same as Example 1.

[0154] Comparative Example 10

[0155] The difference between this comparative example and Example 1 is that the fourth cobalt-containing positive electrode material in the second active coating is replaced by the third cobalt-containing positive electrode material, and the rest is exactly the same as Example 1.

[0156] Performance Testing

[0157] The positive electrode sheets prepared in Examples 1-12 and Comparative Examples 1-10 were assembled into lithium-ion batteries, wherein the negative electrode current collector in the negative electrode sheet used carbon-coated copper foil, the negative electrode active material was fast-charging graphite, the binder was styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC), the conductive agent was Super-P (SP), the mass ratio of fast-charging graphite, SP, SBR and CMC was 95%:1.5%:2.3%:1.2%, and the compaction density of the negative electrode sheet was designed to be 1.5 g / cm 3 The diaphragm used is a ceramic coated diaphragm, and the electrolyte used is an electrolyte that takes both fast charging and high voltage into consideration.

[0158] (I) Room temperature fast charging cycle test

[0159] (a) The battery was left for 30 min; (b) 4C constant current charging to 4.4 V, and then constant voltage charging to 0.05C; (c) left for 30 min; (d) 1C constant current discharge to 3.0 V; From step (a) to step (d) is a cycle of 1 week, and the capacity retention rate of the battery after 500 cycles was recorded.

[0160] (II) High temperature performance test

[0161] First, the battery was tested before high-temperature storage: (a) left for 30 minutes; (b) charged at 1C constant current to 4.4V and then constant voltage to 0.05C; (c) left for 30 minutes; (d) discharged at 1C constant current to 3.0V; (e) left for 30 minutes; (f) charged at 1C constant current to 4.4V and then constant voltage to 0.05C;

[0162] The battery that has undergone steps (a) to (f) is placed in a high temperature storage box and stored at 60° C. for 7 days, and the initial discharge capacity C0 of the battery obtained in step (d) is recorded;

[0163] Then, the battery was tested after being stored at 60°C for 7 days: (g) placed at 25°C for 6 hours; (h) discharged at 1C constant current to 3.0V, and obtained capacity C1; (i) placed for 30 minutes; (j) charged at 1C constant current to 4.4V and then charged to 0.05C at constant voltage; (k) placed for 30 minutes; (l) discharged at 1C constant current to 3.0V, and obtained capacity C2;

[0164] After steps (g) to (l), the capacity retention rate and capacity recovery rate after storage are calculated, wherein the capacity retention rate is the ratio of C1 to C0, and the capacity recovery rate is the ratio of C2 to C0.

[0165] (III) Power performance test

[0166] (a) 30 min standby; (b) 1C constant current charge to 4.4 V and then constant voltage to 0.05C; (c) 30 min standby; (d) 1C constant current discharge to 3.0 V; (e) 30 min standby; (f) 1C constant current charge to 4.4 V and then constant voltage to 0.05C; (g) 30 min standby; (h) 1C constant current discharge to 50% SOC; (i) 60 min standby; (j) 4C constant current charge for 10 s; (k) 60 s standby; (l) 4C constant current discharge for 10 s;

[0167] After steps (a) to (l), calculate the charging DC internal resistance (DCR).

[0168] Some parameters of Examples 1-12 and Comparative Examples 1-10 are shown in Table 1, and the corresponding test results are shown in Table 2.

[0169] Table 1 Partial parameter table of Examples 1-12 and Comparative Examples 1-10

[0170]

[0171]

[0172] Table 2 Performance data of Examples 1-12 and Comparative Examples 1-10

[0173]

[0174]

[0175] analyze:

[0176] It can be seen from the data results of Examples 1-5 and Example 12 that in the positive electrode plate of the present invention, two types of nickel cobalt manganese oxide lithium positive electrode materials with different cobalt contents and particle sizes are used in the first active coating and the second active coating, respectively. By combining the "low cobalt content and large particle size" cobalt-containing material with the "high cobalt content and small particle size" cobalt-containing material in each coating layer, and the combination between the two coating layers, the cost of the positive electrode material can be reduced while ensuring the energy density, and the prepared battery can exhibit excellent high-voltage cycle performance, fast charging performance, high temperature performance and power performance.

[0177] It can be seen from the data results of Examples 1 and 6-7 that by regulating the content of the first cobalt-containing positive electrode material with "low cobalt content and large particle size" in the first active coating, the cycle stability, high temperature performance and power performance of the battery under high voltage can be regulated; when the content of the first cobalt-containing positive electrode material with "low cobalt content and large particle size" is 50-90%, the positive electrode sheet and the assembled battery will be given better cycle stability, better high temperature performance and power performance under high voltage.

[0178] It can be seen from the data results of Example 1 and Examples 8-9 that by regulating the content of the third cobalt-containing positive electrode material with "low cobalt content and large particle size" in the second active coating, the cycle stability, high temperature performance and power performance of the battery under high voltage can be regulated; when the content of the third cobalt-containing positive electrode material with "low cobalt content and large particle size" is 10-50%, the positive electrode sheet and the assembled battery will be given better cycle stability, better high temperature performance and power performance under high voltage.

[0179] From the data results of Examples 1 and 10-11, combined with the data results of Examples 2-5, it can be seen that by adjusting the mass proportion of the second active coating, the cycle stability, high temperature performance and power performance of the battery under high voltage can be adjusted; when the mass proportion of the second active coating is 55-95%, the positive electrode sheet and the assembled battery will be given better cycle stability, better high temperature performance and power performance under high voltage.

[0180] It can be seen from the data results of Example 1 and Comparative Examples 1-10 that when only the first active coating or the second active coating is used, or when the first coating and / or the second coating contains only one cobalt-containing positive electrode material, or when the composite active coating contains only one cobalt-containing positive electrode material, the battery's fast charging performance, cycle performance, high temperature performance and power performance will deteriorate.

[0181] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode plate comprises a current collector and a composite positive electrode active coating disposed on at least one side surface of the current collector; The composite positive electrode active coating comprises a first active coating and a second active coating, wherein the first active coating is disposed on the surface of the current collector, and the second active coating is disposed on the surface of the first active coating away from the current collector; The first active coating layer comprises a first cobalt-containing positive electrode material and a second cobalt-containing positive electrode material; the first active coating layer comprises a third cobalt-containing positive electrode material and a fourth cobalt-containing positive electrode material; The first cobalt-containing positive electrode material, the second cobalt-containing positive electrode material, the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material independently include lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide; Based on the total molar amount of metal elements other than lithium as 100%, the cobalt content of the first cobalt-containing positive electrode material is 5-10%; The cobalt content of the second cobalt-containing positive electrode material is 15-20%, based on the total molar amount of the metal elements other than lithium as 100%; The cobalt content of the third cobalt-containing positive electrode material is 5-10%, based on the total molar amount of metal elements other than lithium as 100%; Based on the total molar amount of metal elements other than lithium as 100%, the cobalt content of the fourth cobalt-containing positive electrode material is 15-20%; Based on the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material as 100%, the mass fraction of the first cobalt-containing positive electrode material is 50-90%; Based on the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material being 100%, the mass fraction of the third cobalt-containing positive electrode material is 10-50%; The D50 particle size of the first cobalt-containing positive electrode material is 4-5 μm; The D50 particle size of the second cobalt-containing positive electrode material is 3-3.8 μm; The D50 particle size of the third cobalt-containing positive electrode material is 4-5 μm; The D50 particle size of the fourth cobalt-containing positive electrode material is 3-3.8 μm; Taking the total mass of the first active coating and the second active coating as 100%, the mass fraction of the second active coating is 55-95%.

2. The positive electrode sheet according to claim 1, characterized in that: The first cobalt-containing positive electrode material, the second cobalt-containing positive electrode material, the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material are all single crystal materials.

3. The positive electrode sheet according to claim 1, characterized in that: The chemical formulas of the first cobalt-containing positive electrode material, the second cobalt-containing positive electrode material, the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material are independently Li z Ni x Co y M (1-x-y) O2, wherein M includes Mn and / or Al, 1.03≤z≤1.07, 0.6≤x≤0.7, 0.05≤y≤0.

2.

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: Based on the total mass of the first cobalt-containing positive electrode material and the second cobalt-containing positive electrode material being 100%, the mass fraction of the first cobalt-containing positive electrode material is 60-80%.

5. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The third cobalt-containing positive electrode material and the first cobalt-containing positive electrode material have the same cobalt content and particle size.

6. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The fourth cobalt-containing positive electrode material and the second cobalt-containing positive electrode material have the same cobalt content and particle size.

7. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: Taking the total mass of the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material as 100%, the mass fraction of the third cobalt-containing positive electrode material is 20-40%.

8. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: Taking the total mass of the first active coating and the second active coating as 100%, the mass fraction of the second active coating is 60-70%.

9. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: Taking the total mass of the first active coating and the second active coating as 100%, the total mass fraction of the first cobalt-containing positive electrode material, the second cobalt-containing positive electrode material, the third cobalt-containing positive electrode material and the fourth cobalt-containing positive electrode material is 94-97%.

10. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The single surface density of the first active coating is 3.45-5.6 mg / cm 2 .

11. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The single surface density of the second active coating is 6.9-9.8 mg / cm 2 .

12. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The single-surface density of the composite positive electrode active coating is 11.5-14 mg / cm 2 .

13. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The compaction density of the composite positive electrode active coating is 3.3-3.5 g / cm 3 .

14. A method for preparing a positive electrode sheet according to any one of claims 1 to 13, characterized in that: The preparation method comprises: Applying a first active coating slurry and a second active coating slurry on at least one side of the current collector, wherein the coating of the first active coating slurry and the second active coating slurry is performed by method one or method two, and drying to obtain the positive electrode sheet; Wherein, the first method includes: applying a first active coating slurry and a second active coating slurry at the same time, wherein the first active coating slurry is applied on the surface of the current collector, and the second active coating slurry is applied on a side of the first active coating slurry away from the current collector; The second method includes: firstly applying a first active coating slurry, drying to obtain a first active coating, and then applying a second active coating slurry on a surface of the first active coating away from the current collector.

15. The preparation method according to claim 14, characterized in that: The viscosity of the first active coating slurry is 7000-12000 mPa·s.

16. The preparation method according to claim 15, characterized in that: The viscosity of the first active coating slurry is 8000-10000 mPa·s.

17. The preparation method according to claim 14, characterized in that: The viscosity of the second active coating slurry is 2000-6000 mPa·s.

18. The preparation method according to claim 17, characterized in that: The viscosity of the second active coating slurry is 3000-5000 mPa·s.

19. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • A method for preparing high-voltage nickel-cobalt-manganese-lithium cathode material

    CN104051725B

  • Method for treatment on high-voltage Ni-Co-Mn ternary positive electrode material by surface drying method

    CN105374996A

  • Positive pole piece and preparation method thereof, lithium ion battery containing positive pole piece and application of lithium ion battery

    CN111864179A

  • Positive plate and application thereof

    CN112531151A